2011 Florida Population Growth Is Third Largest in United States ... But Still Not Close to Pre-Recession Levels - Rodney L. Clouser (EDIS)
Overall, from July 1, 2010 to July 1, 2011 Florida’s population increased by almost 219,000 people, which was the third largest increase in all US states. In this 4-page fact sheet, UF/IFAS economist Rodney L. Clouser explores the implications of this trend. Published by the UF Department of Food and Resource Economics, March 2012.